Determination of Thermodynamic Parameters of Polylactic Acid by Thermogravimetry under Pyrolysis Conditions - Paul Palmay (MDPI AG, 2021)
In the present study, the thermodynamic parameters of Polylactic Acid (PLA) under conditions of thermal degradation were determined. The PLA material, previously sampled and characterized, was analyzed by dynamic thermogravimetry (TG) at heating rates of 5, 10 and 15 °C min−1 with a nitrogen flow of 20 mL min−1 from a temperature of 25 to 900 °C. The data were treated using isoconversional kinetic models to obtain the activation energy and the pre-exponential factor of each model. To fit the DTG curves, the Arrhenius equation was used applying the Contraction Sphere reaction model: two-dimensional phase limit reaction (R2). The thermodynamic parameters such as enthalpy, Gibbs free energy and entropy were determined from the kinetic parameters of suitable models for each heating rate after statistical validation and comparison with other studies. The results showed that as the heating rate increases, the degradation temperature also increases, while the activation energy, enthalpy and pre-exponential factor decrease. According to the value of ∆G (171.65 kJ mol−1), PLA has a significant potential to be used as a raw material to produce bioenergy/biofuels by pyrolysis.